(untitled) (European Journal of Economics, Finance and Business Development, 2024)
This work is dedicated to analyzing the mechanisms of interaction between the Republic of Uzbekistan and foreign countries in the field of external labor migration. In the context of contemporary global challenges and changes in international politics and economics, particular attention is paid to studying agreements, regulatory mechanisms, and partnership relations in the migration sphere between Uzbekistan and foreign countries. Both bilateral agreements and participation in international organizations on migration issues are analyzed. Special focus is placed on practical mechanisms for protecting the rights and interests of Uzbek labor migrants abroad, including social security, medical services, and legislative protection. The paper provides an overview of existing problems and challenges, as well as offers recommendations for improving the effectiveness of interaction mechanisms with foreign partners in the field of external labor migration for mutual benefits and sustainable development.